Development of Activated Carbon from Lemang bamboo (Schizostachyum brachycladum) to Absorb Synthetic Pollutant Methylene Blue - Sokarno, Muhammad Naim Najmie; Yusvana, Rama (Progress in Engineering Application and Technology, 2026)
This paper examines the creation of sustainable activated carbon from Schizostachyum brachycladum (Lemang bamboo) as an eco-friendly adsorbent for the removal of pollutants from wastewater using Methylene Blue as synthetic pollutant. To address the environmentally associated problems of conventional coal-based activated carbon, this study employed a physical activation process using superheated steam at 750°C for the preparation of the adsorbent. The study extensively analysed the physicochemical properties of the processed AC through Scanning Electron Microscopy (SEM), Fourier-Transform Infrared (FTIR) spectroscopy, and X-ray Diffraction (XRD) analyses to examine the surface properties and functional groups. Moreover, this study examined the effects of the particle size (ranging 1-3 mm) of the adsorbent on the efficiency of the process and the regenerability of the adsorbent through temperature treatments in several cycles. The experiment showed that the process obeyed the Langmuir isothermal equation with a very high correlation coefficient (R2 = 0.9988), indicating monolayer adsorption, while it obeyed pseudo-second-order kinetics. Finally, this research work proves that Lemang bamboo is an ideal, affordable, and sustainable source for the preparation of high-quality activated carbon with promising applications for sustainable wastewater treatments.